2016
DOI: 10.1016/j.scs.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A thermal performance parametric study of window type, orientation, size and shadowing effect

Abstract: Windows are one of the elements that greatly influence the performance of buildings, both in terms of thermal comfort and energy consumption for heating or cooling. It is therefore important to find an optimal design that balances their orientation, dimension and shadowing. This paper presents a methodology for the parametric study of a window optimal dimension, based on the thermal performance of a reference room located in the climate region of Coimbra, Portugal. First, the parameters of opening type, orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 32 publications
0
31
0
4
Order By: Relevance
“…On the other hand, regardless the climate conditions, the optimal W W R may be doubled for the simultaneous effect of an improvement of the envelope features and of an enhancement of the installed lighting electric power. Amaral et al [9] performed a parametric study of a reference room where the window size, orientation, and shadowing are analyzed for three types of glazing in Coimbra, Portugal. The authors concluded that lower U -values of the windows contributes to have smaller windows facing south, west, and east orientations and larger windows facing north; being the south orientation the one which contributes higher to the space thermal performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, regardless the climate conditions, the optimal W W R may be doubled for the simultaneous effect of an improvement of the envelope features and of an enhancement of the installed lighting electric power. Amaral et al [9] performed a parametric study of a reference room where the window size, orientation, and shadowing are analyzed for three types of glazing in Coimbra, Portugal. The authors concluded that lower U -values of the windows contributes to have smaller windows facing south, west, and east orientations and larger windows facing north; being the south orientation the one which contributes higher to the space thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…These indexes, when correlated with the energy consumptions, can be useful to draw guidelines that point out the way for better building performances [9][10][11][12][13][14][15], thus helping designers to explore alternative forms and designs. In the specific case of Mediterranean climates, it is interesting to understand which are the most adequate thermal transmittance values of the buildings' elements that decrease the heating demands without excessively raising the cooling needs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have studied effect of various housing design parameters on the thermal performance. These parameters included orientation of building, typology of housing, insulations, effect of various microclimates, window types and sizes, effect of shadowing and so forth [15][16][17][18][19]. Most of the research apply virtual simulation model and generative method, which could generate large set of synthetic dataset while some are using scaled models to place in wind tunnels with controlled environment [11,19].…”
Section: Malaysia Hot Humid Climatementioning
confidence: 99%
“…The author determined that these factors have a high effect on the U -value, particularly 1 for roofs and walls facing West and East orientations. Amaral et al [9] found that double and triple 2 glazing windows facing North contribute positively to the zone thermal comfort, due to the diffuse 3 solar radiation gains being greater than the losses by thermal transmittance, in Coimbra (Portugal).…”
Section: Introductionmentioning
confidence: 99%